Analisis Efisiensi Pemasaran Ayam Broiler (Gallus domesticus) di Kecamatan Sumberjambe Kabupaten jember - Afrilta Rahman, Vany; Yasin, Mochammad (KUBIS, 2021)
Broilersare a type of superior breed resulting from crosses from types of chickens that have high productivity, especially in producing chicken meat. Jember Regency is the district for the highest broiler production. The purpose of this study was to determine the analysis of the marketing efficiency of broiler chickens (Gallus domesticus) in Sumberjambe District, Jember Regency. This method uses snowball sampling. The results of the analysis that has been carried out through the operational efficiency channel, channel III is said to be the most efficient channel for marketing broiler chickens in Sumberjambe District, Jember Regency by using marketing margin measurement tools, farmer's share, and marketing efficiency analysis. Keywords: efisiensi pemasaran, Ayam Broiler, margin pemasaran, farmer’s share